Ecologization of production as an innovative direction for the development of domestic business entities - Butko , N. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2022)
The necessity of compliance with environmental standards in the process of production activities of agricultural business entities in order to ensure their successful functioning is substantiated. It has been studied that the approach to the production of environmental products, is innovative due to the application of measures that cause minimal damage to the environment.  Ecologization of agricultural production involves restoring the agro-resource potential of land, preserving the environment and growing quality and safe food. It was found out that ecologization of production in the agricultural sector is formalized in the concept of organic production, which embodies the idea of a healthy lifestyle and nutrition. It is highlighted that organic production ensures the manufacture and sale of organic products that are obtained as a result of certified production within the legally established procedures. It is substantiated that ecologically oriented management is an important direction of innovative development of the agricultural sector enterprises and it is closely related to the environmental aspects of the use of their lands. The study of the indicators of the development of organic production in Ukraine showed the distribution of operators of certified subjects of the organic market of the country by their number and the total area of agricultural land in 2021. The factors that constrain the development of organic production of domestic business entities are shown. It is noted that the production of organic products brings much higher profits to agricultural producers compared to the traditional one and the reasons for the profitability of such ecological systems are described. To ensure the effective ecologization of production, domestic business entities should search for innovative forms of economic and organizational cooperation among themselves. Such interaction will be a priority area for innovative development of agricultural sector enterprises, which will allow to realize ecological balance in agro-ecosystems. The aspects of stimulating the ecologization of production within enterprises that  have chosen an innovative way of development are described. These are organizational, managerial, environmental, geographical and economic and legal features of the development of ecologically-oriented business entities.